2021
DOI: 10.3390/biomedicines9091185
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic and Anti-Inflammatory Effects of the Synthetic Neurosteroid Analogue BNN27 during CFA-Induced Hyperalgesia

Abstract: Dehydroepiandrosterone (DHEA), an adrenal and neurosteroid hormone with strong neuroprotective and immunomodulatory properties, and ligand for all high-affinity neurotrophin tyrosine kinase receptors (Trk), also exerts important effects on hyperalgesia. Its synthetic, 17-spiro-epoxy analogue, BNN27, cannot be converted to estrogen or androgen as DHEA; it is a specific agonist of TrkA, the receptor of pain regulator Nerve Growth Factor (NGF), and it conserves the immunomodulatory properties of DHEA. Our study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Accumulating evidence has indicated that the injection of CFA into the rodent hind paw could lead to sustained inflammation characterized by persistent hypersensitivities 19,20 . For example, nerve growth factor (NGF) is considered a crucial factor in inflammation and hyperalgesia, and its level was elevated in the paws of inflamed rats treated with CFA 34 . In addition, elevated NGF expression was also detected in rodent DRG after administration of CFA, which induces sensitization of transient potential receptor V1 (TRPV1) and/or A1 (TRPA1)‐positive DRG sensory neurons and in turn facilitates the transmission of pain signals to the central nervous system 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has indicated that the injection of CFA into the rodent hind paw could lead to sustained inflammation characterized by persistent hypersensitivities 19,20 . For example, nerve growth factor (NGF) is considered a crucial factor in inflammation and hyperalgesia, and its level was elevated in the paws of inflamed rats treated with CFA 34 . In addition, elevated NGF expression was also detected in rodent DRG after administration of CFA, which induces sensitization of transient potential receptor V1 (TRPV1) and/or A1 (TRPA1)‐positive DRG sensory neurons and in turn facilitates the transmission of pain signals to the central nervous system 35 .…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 For example, nerve growth factor (NGF) is considered a crucial factor in inflammation and hyperalgesia, and its level was elevated in the paws of inflamed rats treated with CFA. 34 In addition, elevated NGF expression was also detected in rodent DRG after administration of CFA, which induces sensitization of transient potential receptor V1 (TRPV1) and/or A1 (TRPA1)‐positive DRG sensory neurons and in turn facilitates the transmission of pain signals to the central nervous system. 35 Thus, the CFA‐induced chronic pain rat model is commonly regarded as an inflammatory pain model.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation also induced mechanical and thermal hyperalgesia accompanied by increased IL-6 and TNF-α in the mice plasma, suggesting EA as an anti-inflammatory technique. Recently articles reported that local inflammation in mice increased circulating IL‑6 and TNF-α levels 34 . Additionally, although the administration of IL-6 induced mechanical and thermal hyperalgesia, IL-6 blockage produced analgesic effects 35 .…”
Section: Discussionmentioning
confidence: 99%
“…All the tissues had 2-3 mm thickness. Total RNA was extracted from the tissues with TRIzol reagent (Invitrogen Life Technologies), and cDNAs were synthesized using TAKARA PrimeScript 1st strand cDNA synthesis kit (Takara Bio) (19). Expression of each gene of interest was determined using SYBR Green master mix (Kapa Biosystems) containing a specific set of primers in a final volume of 10 µl.…”
Section: Methodsmentioning
confidence: 99%